A Prática de atividades corporais alternativas em Maceió.Gosto e ou utilidade? - Neri, Nilson Monteiro (2009)
The aim of this study is to draw a panorama of socio-anthropological practices body matrix east, working in the city of Maceio. Seek a few observations from the perspectives of descriptive and exploratory study, aiming also consider the analysis in terms of formation of a cultural field (Bourdieu) that is correlated, and which we believe have strong ties either with the condition / status of its adherents, and cultural affinities with the east disseminated within these practices. Therefore the study has interference víeis social sciences with emphasis in sociology. We observed several common procedures for social research in the basement of bodily practices, with data on the practitioners in the city of Maceio. This study came to a subsidy of discussion in Physical Education with breaking the sociological paradigm of simplistic biologism hitherto much used. This study comes from the idea department to enter a line of vision research, emphasizing the identity, the urban and cultural issue, which is the focus of there search dissertation.